Is the pinatubo God angry? = Galit ba ang Diyos ng pinatubo? Simkin Angelo S. de Pio. - Talisayon, Vivien (Science supplementary materials for the k to 12 curriculum, 2014)
The story brings out a cultural dimension that is outside the domain of science and, thus, is not confirmed nor denied. However, the story gives a scientific explanation of the eruption of Mount Pinatubo on June 12, 1991, which had worldwide effects. The book can be made interactive by pausing on pages 6-8 and asking the children what they think about the Pinatubo god. After pages 11-12, children can also be asked what they think is the scientific explanation for the Mt. Pinatubo eruption. This story may be used as motivation, supplementary materials, or part of lessons in Grade 6 as shown below.